Social Cost of Improper Land and Variety Selection in Paddy Production in Turkey - Gunduz, Orhan; Ceyhan, Vedat; Dengiz, Orhan (European Journal of Sustainable Development, 2017)
For last decades, efficient use of land as a natural resources has the priority at the agenda of policy makers. Allocating farm land to optimal crop and selecting proper crop variety is vital to reach not only economically, but also environmentally efficient farming. Therefore, the study examined the social cost of improper land and crop variety selection in paddy production in Samsun province of Turkey. Research data were collected from both field experiment and 45 paddy producers by using questionnaire. Classical economic analysis procedures and cost calculation methods were followed. Economic losses sourced from improper land allocation and wrong variety selection in paddy production was calculated by combining individual and social losses. Research results showed that average paddy producers conducted their activities in S2 class lost 1983 kg per hectare of paddy, which was valued 595, due to improper land and variety selection. 64% of it was sourced from improper land selection, while that of improper paddy variety selection was 36%. However, average paddy producers conducted their activities in S3 class lost 3012 kg of paddy per hectare, which was valued 900. Research results also showed that social cost of improper land and variety selection in Samsun was 2,1 million. 62% of total social cost sourced from S2 class land, while that of S3 and S1 were 23% and 15%, respectively. 24% of the total social cost resulted from opportunity cost, while the rest attributed to improper land and variety selection in paddy production. Completing preparing activities the detail land use map and sharing with farmers in the research area may decrease the social cost of improper land and variety selection. Designing education program for farmers in order to make better variety and land selection and disseminate the information related variety and land selection via extension services may reduce the social cost of improper decision in the research area. Keywords: Turkey, paddy production, economic losses, improper selection, social cost